THE EFFECT OF ORGANIZATIONAL TRUST IN HOUSİNG COOPERATİVES TO THE PERFORMANCE EXPECTED BY THE PARTNERS: A STUDY ABOUT HOUSİNG COOPERATİVES (Third Sector Social Economic Review, 2011)
Cooperative effect occurs from the expectations of partners. Partners expect high-leveled cooperative effect from the cooperative by protecting their purposes and benefits. The expectations of the partners can increase or can decrease by depending on various variables in time.The purpose of this study is to exhibit the effect of organizational trust to the performance expected by the partners. By depending on this purpose, a study was performed. In this study, three hypotheses were made by associating three subdimensions of the organizational trust with the performance. As a result of the analysis about the hypotheses, an expressive and positive relationship was found between the performance expected by the partners and the trusts to the directors of housing cooperative, to the processes of housing cooperative and to the partners of housing cooperative. According to obtained findings, the trust to the directors of housing cooperative affects the performance expected by the partners the most.
Keywords: Organizational Trust; Cooperative; Cooperative Effect; Performance; Housing Cooperative